Emergence of private universities in Nigeria: challenges and prospects / Mustapha Adam Ishola … [et al.] - Ishola, Mustapha Adam; Suleiman, Yusuf; Modupe, Oladimeji Rasheedat; Abubakar, Lawal Abdulmumin; Olohundare, Sulyman Kalmaldeen (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2020)
University education in Nigeria has become a complex enterprise as public universities in the country are not able to absorb and accommodate the demand of all eligible admission seekers to institutions of higher education owing to restricted carrying capacity of the current government owned tertiary institutions. Thus, denationalization of university education has become a global issue and embraced by educational stakeholders as one of the major fastest growing segments of post-secondary education at the turn of the 21st Century. In view of the foregoing, this paper examined the emergence of private universities in Nigeria: Challenges and the prospects. The concept of private university was critically examined taking into cognizance the historical development of university education in Nigeria and its purposes as contained in the National Policy on Education. Also, the evolution, classifications as well as the list of approved private universities as at 2020 in the country were consecutively elucidated. The justifications for the establishment of private universities and the challenges serving as the stumbling blocks to the institutions were looked into. The study concluded that development and production of high-level manpower within the context of the nation’s needs rely heavily on the functionality and effectively of private universities in Nigeria. It was recommended among others that the government must provide technical and logistics support as required by these institutions for effective service delivery; government scholarship as well as bursary awards should be extended to students in the private higher institutions and the management of the institutions should engage in insurance scheme of diverse categories of foreseeable risk can be shared.